Advanced computing technologies and applications proceedings of 2nd International Conference on Advanced Computing Technologies and Applications - - ICACTA 2020 /: proceedings of 2nd International Conference on Advanced Computing Technologies and Applications - - ICACTA 2020. (2020) - Unknown
No abstract available